Impact of Common Law on the Gambian Legal System - Mendy, Ousu (Journal of Humanities and Social Sciences (JHASS), 2025)
The impact of common law system on The Gambia is manifest in the type of legal system the country embraces. Prior to colonialism, The Gambia embraced customary practices of the indigenous people of the country which is mainly influenced by their belief systems in cultural practices. So, customary practices were dominant in the country and they reflected the beliefs of different regions in the country. They also differed from one region to another and from one ethnicity to another. The present existence of the Law of England (Application) Act that allows all the laws operating in Britain as of 1888 to be used in The Gambia is an indication of how common law system gains traction in the country’s legal framework. It is obvious that common law is still alien to the practices in certain regions in The Gambia – especially the provincial part of the country but it is also clear that it contributes to maintenance of peace and justice. On the other hand, it causes social disorder as some societies fiind it inimical to their traditional practices. For example, the criminalization of Female Genital Mutilation (FGM) in 2015 and the current attempt to abrogate this law questions the compatibility of this criminalization with the cultural values of certain indigenous people. Therefore, for the country to strengthen its legal framework, the common law needs to be strengthened by moral values of Gambian society to address its problem of governance.